(untitled) (American Journal of Islam and Society, 1989)
David S. Powers’ book, originally a doctoral dissertation submitted to Princeton University, is a welcome addition to the already growing corpus of studies revising Joseph Schacht’s thesis that Islamic law did not exist during the lifetime of the Prophet. This is, however, not the central theme of the book. Powers contends that the Islamic law of inheritance is not identical to the system of inheritance revealed to Prophet Muhammad and that the Muslim community is not in possession of the original reading and understanding of several Qur’anic verses and Prophetic hadith. The thesis presented in this book can be summarized as follows: Islamic law began to develop with Qur‘anic legislation which was more clear and systematic on the subject of inheritance. In pre-Islamic Arabia the intergenemtional transmission of property was by seniority rather than by direct descent. The Qur’an introduced a new system of inheritance which reflected a transition from tribalism to individualism, with more emphasis on the rights of women to property. The author sees two systems of the law of inheritance in Islam: 1) The proto-Islamic law of inheritance which existed only during 2) Islamic law of inheritance, which exists as ‘ilm al-farii‘id. the lifetime of the Prophet; and, Powers contends that the proto-Islamic system was mainly testatory and the property was distributed according to fixed shares only in the absence of a will. Husband and wife, not being blood relatives, inherited as testatory heirs. The author divides his dissertation into two parts. In the first part he deals with the proto-Islamic, in the second with the Islamic system of inheritance. The first part proceeds by looking at the practice of bequest and testation in Makkah and Madinah in early Islam, giving special attention to the inheritance between husbands and wives, and the Qur’anic law of testation and intestacy. The second part proceeds by looking at socio-economic developments in the early period and contends that people in power manipulated the Qur‘anic ...